ANALYSIS OF LEGAL PROTECTION FOR JUVENILE CLIENTS INVOLVED IN NARCOTICS OFFENSES THROUGH PSYCHOSOCIAL GUIDANCE USING CUENTO THERAPY - Salma Wulandari; Bambang Hartono (Universitas Nusa Cendana, 2026)
This study examines legal protection for children involved in narcotics offenses at the Class I Bandar Lampung Probation Office, emphasizing not only legal assistance but also psychosocial support as part of child development. The research focuses on analyzing the factors that lead children to engage in narcotics offenses and evaluating the implementation of psychosocial guidance using cuento therapy as a preventive and rehabilitative approach. Using a qualitative descriptive method, data were collected through in-depth interviews, observation, and document analysis. The study is grounded in the legal protection theory of Philipus M. Hadjon and psychosocial counseling theory. The findings reveal that cuento therapy is an effective tool for both preventive and repressive legal protection. Through narrative-based interventions, children are encouraged to reflect on their actions, develop self-control, reduce psychological distress, and internalize moral values in a non-intimidating manner. This approach supports mental recovery, lowers the risk of reoffending, and facilitates smoother social reintegration. However, several challenges remain, including limited time for counseling sessions, difficulties in monitoring due to children’s school activities, and geographical barriers between clients’ homes and the probation office. In conclusion, integrating psychosocial guidance with legal protection provides a more holistic and child-centered approach within the juvenile justice system. This model prioritizes the best interests of the child while supporting rehabilitation and long-term behavioral change. Keywords: Legal Protection; Juvenile Narcotics Offenders; Psychosocial Guidance;Cuento Therapy; Probation Office